INTERNALISASI NILAI-NILAI AKHLAK DALAM SURAT AL- HUJURAT MENURUT SAYYID QUTHUB - Hariyanto, Toto (JIA (Jurnal Ilmu Agama), 2015)
This article tries to analyse on the process of internalization of akhlaq (code of behavior) values on the Quranic Sural Al Hujarat according to Saayid Qutb. It is qualitive research based on the library research. The research finds that there are three types of the intrepretation used by sayyid qutub. The methods are takhalli tahalli and tajalli.